Peran Komisi Yudisial dalam Pengawasan Integritas Hakim Agung di Mahkamah Agung - Rokilah Rokilah; Fitria Agustin; Endra Budiantono (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The Judicial Commission was established based on the Indonesian constitution, namely the 1945 Constitution of the Republic of Indonesia, with the aim of improving the quality of judges and also maintaining the dignity of the judiciary in Indonesia so that it remains independent, clean and authoritative. Supervision of the law is carried out by the Judicial Commission specifically to address ethical violations of judges. These violations can arise in decisions or behavior as judicial officials. This study uses a qualitative method, with a normative type of research, namely legal research that emphasizes the review of legal documents and library materials related to the main problem. The research approach used is the statute approach. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The purpose of the study is to determine the Role of the Judicial Commission in Supervising the Integrity of Supreme Court Justices at the Supreme Court and to determine the Judicial Commission's supervision of Supreme Court Justices in the independence of the Supreme Court as an executor of judicial power. The results of the study indicate that 1) the Judicial Commission is functionally only as a support for the judicial power institution. The Judicial Commission is not an institution that enforces legal norms, but rather an institution that enforces ethical norms. The Judicial Commission also functions to maintain the independence of judges in issuing decisions from political intervention. and 2) Supervision carried out by the Judicial Commission on supreme court judges is often debated in relation to the independence of the judiciary.